The difference of physical fitness of short stature children with and without Channa striata extract (CSE) supplementation - Faiza, Arif; Anam, Mohammad Syarofil; Soetadji, Anindita; Mexitalia, Maria (Medica Hospitalia : Journal of Clinical Medicine, 2021)
Background: Physical fitness affected by aortic elasticity which is increased appropriately with insuline growth factor-1 (IGF-1). Channa striata extract (CSE) supplementation increased arginine serum level and further lead to increase of IGF-1, endothelial dysfunction remodeling, and physical fitness. The current study aimed to explore the difference of physical fitness of short stature children with and without CSE supplementation. Method: This cross sectional study conducted to 100 short stature children (male 58; female 42; CSE 50; placebo 50) aged 8-12 years in Brebes, Central Java Indonesia. Short stature was defined as the height/age Z score between -2 and -3 based on WHO 2007 growth chart standard. Physical fitness was measured by modified Harvard step test as stated as VO2max, physical activity by physical activity record and stated as physical activity level (PAL). Data was analyzed by independent t-test and Pearson correlation. Results: VO2max level was higher in CSE 41.67 ± 6.967 ml/kg/minutes and placebo 41.16 ± 5.238 mL/kg/minutes, p=0.682. Hemoglobin level was higher in CSE than placebo (13.12 ± 0.932; 12.99 ± 0.878) g/dL; p=0.5020. All children revealed active category on PAL. The results showed a significant relationship between PAL and physical fitness, hemoglobin and PAL on CSE (p<0.05), however there was no correlation between hemoglobin level and physical fitness. Conclusion: Physical fitness in short stature children with CSE supplementation or placebo was good category. There was no differences between hemoglobin level and PAL in both of groups. There was no difference between physical fitness in short stature children with CSE supplementation or placebo. Keywords: physical fitness, short stature, physical activity, hemoglobin level